Analisis Bentuk Perubahan Makna Kata Bahasa Indonesia pada Platfrom Instagram - Trisnawati Bura; Palmavita, Maria; Rabita Isnanda; Fatimatul Jahro; Yosefa De Ancieta (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is a communication tool in the form of a system of sound symbols produced from human speech. Changes in meaning in Indonesian can be classified into five as follows: widening meaning change, narrowing meaning change, refining meaning change, roughening meaning change and total change. This research uses a qualitative method, which is characterized by descriptive analysis. The data is sourced from the Instagram platform with the collection technique through the note-taking method. After the data is collected, the data is processed, reducing data, presenting data and making conclusions based on the information that has been obtained. Based on the results and discussion, it can be concluded that there are 5 types of word meaning changes found on the Instagram social media platform. The five types of meaning changes include widespread/generalized meaning changes, narrowed/specialized meaning changes, refined/euphemia meaning changes, coarsening/dysfemia meaning changes and total meaning changes. The changes in meaning found on the Instagram social media platform are 29 words that experience changes in meaning with 16 words that experience changes in widespread meaning, 3 words that experience changes in narrow meaning, 4 words that experience changes in refinement meaning, 3 words that experience changes in coarsening meaning, and 3 words that experience changes in meaning in total